Persepsi Lansia Terhadap Penggunaan Terapi Komplementer Dan Alternatif Sebagai Mitigasi Masalah Kesehatan - Nurhidayati, Istianna; Muflih, Muflih; Erwanto, Rizky (Yayasan Healing and Healthcare Education, 2024)
Elderly individuals may have varying perceptions of complementary and alternative therapies available in Indonesia. This study aims to explore the elderly's perceptions regarding the use of complementary and alternative therapies as an effort to mitigate health issues. The research method employed is a literature review, identifying relevant articles from various academic databases. Analysis was conducted on gathered data to compile a comprehensive overview of elderly perceptions towards complementary and alternative therapies. Results indicate that most elderly individuals hold a positive view of complementary and alternative therapies as alternatives to enhance their quality of life. Implications of this research provide a basis for developing more inclusive health policies and a more holistic approach to elderly care.